Comprehensive analysis of etiology, prognosis and clinical outcome of acute pancreatitis in a tertiary care center - Duraisami, Vinodh; Balraj, Gunasekaran; Rengan, Vinyak (International Surgery Journal, 2018)
Background: Acute pancreatitis can be classified as mild and severe. Mild pancreatitis is explained by interstitial edema of the gland and it is usually a self-limiting form. Whereas in severe pancreatitis, there is pancreatic necrosis, severe systemic inflammatory response and multi-organ failure which may lead to mortality. To identify the most common etiological agent of acute pancreatitis in our institution. Methods: Patients diagnosed with acute pancreatitis in Institute of General Surgery, Rajiv Gandhi Govt. General Hospital. 50 of them are to be selected on the basis of nonprobability (purposive) sampling method. Data pertinent to the scoring systems will be recorded within 24 h of admission to the hospital. Results: 86% of patients had BISAP score less than 3 (mild) and 14% of patients had more or more than 3 (severe). The cases with mild, moderate and severe CTSI score were 76%, 20% and 4% respectively. Only two cases with BISAP score 3 or more had CTSI >6. Conclusions: Alcohol is the most common etiological factor for acute pancreatitis in this regional population. The morbidity rate is 26% and the mortality rate in patients with severe pancreatitis was 4%. The BISAP score is more accurate in predicting disease severity and significantly than CTSI in this study.